Diagnostic accuracy of office blood pressure compared to home blood pressure in patients with mild cognitive impairment and dementia - de Heus, Rianne AA (Eur J Cardiovasc Nurs, 2019)
BACKGROUND: Hypertension and cognitive impairment often coexist in older people. Office blood pressure measurement is a poor indicator for diagnosing hypertension in the general population. However, its diagnostic accuracy has not been substantially studied in patients with cognitive impairment. AIM: The aim of this study was to determine the proportion of misdiagnosis of hypertension in patients with mild cognitive impairment and dementia compared to no cognitive impairment, by comparing office blood pressure measurement with home blood pressure measurement. METHODS: A cross-sectional study including consecutive patients visiting a memory clinic between 2014 and 2017. Home blood pressure was measured for one week according to the European guidelines. Office blood pressure was assessed during routine clinical practice. Using guideline definitions for normal blood pressure and hypertension, we investigated the proportion of disagreement between office blood pressure measurement and home blood pressure measurement. Univariable and multivariable logistic regression compared disagreement in diagnosis between patients with dementia, mild cognitive impairment and no cognitive impairment. RESULTS: Of 213 patients (aged 73.4±9.0 years, 42% women) 82 had dementia, 65 had mild cognitive impairment and 66 had no cognitive impairment. Mean office blood pressure was 156/84±23/11 mmHg and mean home blood pressure was 139/79±16/10 mmHg. In 31% of patients, there was disagreement in hypertension diagnosis. This proportion was higher for mild cognitive impairment (38.5%) and dementia (35.4%) compared to no cognitive impairment (18.2%), with adjusted odds ratios of 3.7 (95% confidence interval 1.5–9.0), P=0.005 for mild cognitive impairment and 3.4 (1.3–8.6), P=0.011 for dementia. CONCLUSIONS: In memory clinic patients with dementia and mild cognitive impairment, the diagnostic accuracy of office blood pressure measurement is lower compared to patients without cognitive impairment. To avoid the risk of making improper treatment decisions in this vulnerable group, a diagnosis of hypertension should be based on home blood pressure measurement, not office blood pressure measurement.